Investigation of relationships between removals of tetracycline and degradation products and physicochemical parameters in municipal wastewater treatment plant - Topal, Murat; Senel, Gulsad Uslu; Obek, Erdal; Topal, Isil Arslan (Academic Press Ltd- Elsevier Science Ltd, 2016)
Determination of the effect of physicochemical parameters on the removal of tetracycline (TC) and degradation products is important because of the importance of the removal of antibiotics in Wastewater Treatment Plant (WWTP). Therefore, the purpose of this study was to investigate the relationships between removals of TC and degradation products and physicochemical parameters in Municipal Wastewater Treatment Plant (MWWTP). For this aim, (i) the removals of physicochemical parameters in a MWWTP located in Elazig city (Turkey) were determined (ii) the removals of TC and degradation products in MWWTP were determined (iii) the relationships between removals of TC and degradation products and physicochemical parameters were investigated. TC, 4-epitetracycline (ETC), 4-epianhydrotetracycline (EATC), anhydrotetracycline (ATC), and physicochemical parameters (pH, temperature, electrical conductivity (EC), suspended solids (SS), BOD5, COD, total organic carbon (TOC), NHt -N, No-2(-)-N , No-3(-)-N and O-PO(4)(-)3) were determined. The calculation of the correlation coefficients of relationships between the physicochemical parameters and TC, EATC, ATC showed that, among the investigated parameters, EATC and SS most correlated. The removals of other physicochemical parameters were not correlated with TC, EATC and ATC. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Degradation product; Physico-chemical; Removal; Tetracycline; Wastewater treatment plant